Cranial osteology of the Early Cretaceous Sapeornis chaoyangensis (Aves: Pygostylia). (September 2020) - Hu, Han; O'Connor, Jingmai K.; McDonald, Paul G.; Wroe, Stephen
Abstract: We describe the detailed cranial osteology of Sapeornis chaoyangensis based on information from previously described specimens and IVPP V19058, a specimen that was recently reported with regards to the palatal elements but not fully described. The skull in this specimen is entirely preserved in disarticulation, providing the most comprehensive glimpse into the morphology of the cranial bones and their articulations for this taxon. Based on the new information extracted from this specimen, we revise some interpretations of cranial elements in previously published Sapeornis specimens and provide a comprehensive description of the cranial osteology for this basal pygostylian. The results of this study demonstrate that the postorbital bar, jugal bar, nasal, quadrate, and palate in Sapeornis show the plesiomorphic rigid articulations among birds. The comparison of cranial features across Paraves suggests that major cranial modifications evolved at the base of Ornithothoraces, and primarily in the ornithuromorph lineage.